2015
DOI: 10.1021/acs.langmuir.5b01473
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Chemical Stability of Thiol Bonding on Gold Nanostars

Abstract: The stability of thiol bonding on the surface of star-shaped gold nanoparticles was studied as a function of temperature in water and in a set of biologically relevant conditions. The stability was evaluated by monitoring the release of a model fluorescent dye, Bodipy-thiol (BDP-SH), from gold nanostars (GNSs) cocoated with poly(ethylene glycol) thiol (PEG-SH). The increase in the BDP-SH fluorescence emission, quenched when bound to the GNSs, was exploited to this purpose. A maximum 15% dye release in aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 62 publications
2
84
0
Order By: Relevance
“…The much higher temperature increase achieved on the printed GNS patterns under ambient conditions compared to the values previously reported for GNS in aqueous solutions [17,30] is likely due to the absence of the thermal dissipation from the bulk solvent (water) that has a high thermal capacity compared to air (see the model provided in Supporting Information File 2). …”
Section: Resultsmentioning
confidence: 73%
“…The much higher temperature increase achieved on the printed GNS patterns under ambient conditions compared to the values previously reported for GNS in aqueous solutions [17,30] is likely due to the absence of the thermal dissipation from the bulk solvent (water) that has a high thermal capacity compared to air (see the model provided in Supporting Information File 2). …”
Section: Resultsmentioning
confidence: 73%
“…[54][55][56] SEM imaging showed that the surfaces of substrates fabricated with S-AuNS (Figure 3a) and L-AuNS ( Figure 3d) were densely populated by particles. SAuNS were more homogeneously distributed on the surface of glass substrates compared to L-AuNS, possibly due to an increased propensity of L-AuNS to aggregate in solution before self-assembly.…”
Section: Synthesis Of Self-assembled Monolayers Of Auns Grafted On Glmentioning
confidence: 99%
“…32 bBSA is known to bind to both glass and Au surfaces; on glass, through non-covalent physisorption, while on Au surfaces, through coordinative interaction between gold and the bBSA thiol groups. [54][55][56] When AuNS substrates were coated with bBSA monolayers, their LSPR peak positions were red-shifted by about 6-9 nm, due to the higher refractive index of bBSA compared to air ( Figure S4, Supporting Information). Similarly, a previous report showed bBSA provides a spacing of ~4-8 nm between the dye molecules and the Au surface, while the streptavidin attached to the dyes, provides an additional separation distance of ~4 nm, resulting to a total spacing of ~12 nm.…”
Section: 61mentioning
confidence: 99%
“…A steep temperature increase,turning into a plateau after 15-20 s, was observed in all cases as it shown in The measured values of temperature jump, ΔT max , indicate a photo-thermal effect much more effective than that previously observed in GNS solutions and for GNS monolayers. 10,13 As a comparison, control experiments performed by irradiating the blank paper substrate at the same laser intensities showed almost negligible photothermal effect (ΔT≤0.4°C). A measurable thermal load (ΔT max > 20 o C) was obtained even from the GNS patterns printed with low concentration of inks (C GNS = 0.042 mg/mL).…”
Section: Nir Irradiation Of Printed Gns Patternsmentioning
confidence: 99%
“…within the LSPR of these GNS. 13 The increase of temperature of these GNS solutions under NIR irradiation is shown in Figure 3. The temperature increases following an exponential growth law with average growth times ≅ 120-140 s up to a plateau value.…”
Section: Nir Irradiation Of Printed Gns Patternsmentioning
confidence: 99%